Effects of a Perturbation-Based Balance Training on Compensatory Postural Responses to Backward Loss of Balance in Patients with Cerebellar Disease: A Case Study - Chang-Ha Im; Jin-Hoon Park (Asian Society of Kinesiology, 2021)
OBJECTIVES The damage to the cerebellum primarily results in balance-related abnormalities that may affect performance of locomotion and postural adjustments, eventually contributing to an increased risk of fall and fear of falling in patients with cerebellar disease. The purpose of the present study was to investigate the effect of a perturbation-based training that induced backward loss of balance on compensatory postural responses in patients with cerebellar disease. METHODS The participant was a 51-year-old female diagnosed with spinocerebellar ataxia and had the disease for 19 years. The perturbation-based backward balance training was performed over 8 weeks (a total of 24 training sessions) in order to facilitate the perception of postural perturbation onset and execution of rapid compensatory responses. RESULTS The patient demonstrated a noticeable reduction in the number of steps required to recover body balance after postural disturbances. The reduction of multi-step reactions in recovering balance could be attributed to improvements in the body center-of-mass displacement and trunk control during the landing of step. Besides, there were also improvements in subjective measures of functional mobility and psychological well-being after the balance training. CONCLUSION Although current research evidence of balance rehabilitation for cerebellar patients is lacking, this study offers the feasibility of adaptive training to improve postural stability through task-specific training intervention.